Clinical correlates of plasma insulin levels over the life course and association with incident type 2 diabetes: the Framingham Heart Study. Issue 1 (21st February 2022) - Lieb, Wolfgang; de Oliveira, Camila Maciel; Pan, Stephanie; Echouffo-Tcheugui, Justin Basile; Weber, Katharina Susanne; Vasan, Ramachandran S; Xanthakis, Vanessa
Abstract : Introduction: Insulin is a glucose-lowering hormone that affects carbohydrate, lipid, and protein metabolism. Limited data exist on the correlates of insulin levels over the life course in healthy community-dwelling individuals. Research design and methods: Using multilevel modeling of multiple serial observations over 21 years, we assessed the longitudinal correlates of fasting insulin and the cross-sectional correlates of fasting and 2-hour (2h, post 75 g glucose challenge) plasma insulin concentrations in 2140 relatively healthy Framingham Heart Study participants without diabetes (61% women; mean age, 42 years). We used multivariable-adjusted Cox regression to relate glycemic markers (fasting and 2h-insulin, fasting glucose, 2h-glucose, and hemoglobin A1C ) to the risk of type 2 diabetes during follow-up. Results: Over the life course, fasting insulin concentrations were inversely associated with age, male sex, and physical activity, whereas waist circumference, the total/high-density lipoprotein (HDL) cholesterol ratio, and blood triglycerides were positively associated with insulin levels (p<0.005 for all). Male sex (inversely related) and the total/HDL cholesterol ratio (positively related) emerged as the most important cross-sectional correlates of 2h-insulin (p<0.005 for all). All markers were associated with higher risk of type 2 diabetes (352 cases, median follow-up 18 years, p<0.001 for all). Conclusions: We observed common and distinct correlates of fasting and 2h-insulin levels. Our findings highlight a potential role of insulin in lipid and lipoprotein metabolism. Furthermore, fasting and 2h-insulin are critical markers of future diabetes risk. Further studies are needed to confirm our findings.